REMOTE CONTROLLING PRESENTATION USING ANDROID APPLICAITON - Zahari, Mohamad Firdaus Bin (UNIVERSITI TEKNOLOGI PETRONAS, 2012)
The numbers of smartphone users are increasing day by day. One of the popular operating system used to power the smartphone is Android. Android is maintained and developed by Google which they are providing Android SDK that contains the tools and API needed to develop a custom application. By manipulating the capability to access built-in sensors and reading of the smartphones such as touch screen, phone orientation, accelerometer and GPS, a custom presentation remote controlling application can be developed. This will be proven useful as the users will not have to buy extra remote devices to assist them when they are doing presentation as they can install this application directly to their phones. The application will be designed and develop using Android SDK and coded in Java programming language. Result shows that by manipulating the available sensors on the smartphones, we can utilize the Bluetooth and Wi-Fi functionality of the smartphones to connect with remote computer thus communicating with it. The application will send the data based on user input which then will be interpreted by the server application on the remote computer to control the slide presentation. The elements in this report contain introduction, problem statement, objectives, literature review and methodology which are used to develop the application. The discussion of the obtained results will be looked further in this project.